2003
DOI: 10.1016/s0020-7292(03)00159-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac disease in pregnancy

Abstract: Rheumatic heart disease was the predominant type. Patients in NYHA class I/II had a better maternal and fetal outcome than those in NYHA class III/IV. Surgical correction of the cardiac lesion prior to pregnancy was associated with better pregnancy outcome. Pregnant women with prosthetic valves tolerated pregnancy well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
119
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(140 citation statements)
references
References 18 publications
19
119
0
2
Order By: Relevance
“…A number of studies have shown that medical co‐morbidities such as hypertension,9 cardiac disease,25 asthma,26 inflammatory disease,11 mental health problems,27 infection,9 musculoskeletal disorders11 and neurological conditions11 were associated with maternal morbidity and mortality. In contrast to some previous literature this study did not find an association between obesity and maternal mortality 17.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that medical co‐morbidities such as hypertension,9 cardiac disease,25 asthma,26 inflammatory disease,11 mental health problems,27 infection,9 musculoskeletal disorders11 and neurological conditions11 were associated with maternal morbidity and mortality. In contrast to some previous literature this study did not find an association between obesity and maternal mortality 17.…”
Section: Discussionmentioning
confidence: 99%
“…Bhatla et al [21] showed that there were more fetal complications, as well as more preterm and low-birth-weight neonates, among patients in NYHA class III/IV than among those in NYHA class I/II. The incidence of premature delivery was elevated among patients with HF in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…1 Physiological changes of pregnancy worsen the cardiac symptoms especially in the third trimester. Obstetrical and neonatal complications also occur more frequently in women with heart disease.…”
Section: Discussionmentioning
confidence: 99%